Analysis of Service Quality Improvement Using the Six Sigma Method in the Hotel Four Seasons Resort at Jimbaran Bay - P W Y Kencana; I P M Astawa; I M Wijana (Jurusan Akuntansi Politeknik Negeri Bali, 2020)
The purpose of this research is to determine the level of service quality applied at the Four Seasons Resort Hotel at Jimbaran Bay with the Six Sigma method. This research applies Six Sigma as a method to improve the quality of services of the Four Seasons Resort Hotel at Jimbaran Bay, specifically to meet customer expectations so that customers feel satisfied with the services provided. The results showed that the Four Seasons Resort Hotel at Jimbaran Bay had a DPMO value of 201.944, if converted it showed a Six Sigma value of 2,34 on a satisfaction target of 5 or very satisfied. Based on the Fishbone diagram, the order of problems that dominates must be resolved is the evaluation of services and facilities, standardization of time or improvement of administrative procedures, and allocation of vacant room items.